Impact of molecular alterations on quality of life and prognostic understanding over time in patients with incurable lung cancer: a multicenter, longitudinal, prospective cohort study - Kuon, Jonas; Blasi, Miriam; Unsöld, Laura; Vogt, Jeannette; Mehnert, Anja; Alt-Epping, Bernd; van Oorschot, Birgitt; Sistermanns, Jochen; Ahlborn, Miriam; Ritterbusch, Ulrike; Stevens, Susanne; Kahl, Christoph; et al. (European radiology, 2021)
Purpose  The purpose of this study is to investigate changes over time in quality of life (QoL) in incurable lung cancer patients and the impact of determinants like molecular alterations (MA). - Methods  In a prospective, longitudinal, multicentric study, we assessed QoL, symptom burden, psychological distress, unmet needs, and prognostic understanding of patients diagnosed with incurable lung cancer at the time of the diagnosis (T0) and after 3 (T1), 6 (T2) and 12 months (T3) using validated questionnaires like FACT-L, National Comprehensive Cancer Network (NCCN) Distress Thermometer (DT), PHQ-4, SCNS-SF-34, and SEIQoL. - Results  Two hundred seventeen patients were enrolled, 22 (10%) with reported MA. QoL scores improved over time, with a significant trend for DT, PHQ-4, and SCNS-SF-34. Significant determinants for stable or improving scores over time were survival > 6 months, performance status at the time of diagnosis, and presence of MA. Patients with MA showed better QoL scores (FACT-L at T1 104.4 vs 86.3; at T2 107.5 vs 90.0; at T3 100.9 vs 92.8) and lower psychological distress (NCCN DT at T1 3.3 vs 5; at T2 2.7 vs 4.5; at T3 3.7 vs 4.5; PHQ-4 at T1 2.3 vs 4.1; at T2 1.7 vs 3.6; at T3 2.2 vs 3.6), but also a worsening of the scores at 1 year and a higher percentage of inaccurate prognostic understanding (27 vs 17%) compared to patients without MA. - Conclusion  Patients with tumors harboring MA are at risk of QoL deterioration during the course of the disease. Physicians should adapt their communication strategies in order to maintain or improve QoL.
Gesehen am 15.08.2023